LINGVOCULTUROLOGICAL INTERPRETATION OF RELIGIOUS-NATIONAL CONCEPTS IN THE WORKS OF MURAD MUHAMMAD DO’ST - A.K. Khamidov (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
This thesis provides a lingvoculturological analysis of religious-national concepts in the literary output of Murad Muhammad Do'st, a prominent Uzbek writer whose works reflect the interplay of Islamic spirituality, national identity, and cultural heritage amid Uzbekistan's socio-political transitions. Examining key texts such as the novel "Lolazor" (1988) and the trilogy "Abdullajon" (2005), the study dissects linguistic constructs—metaphors, idioms, and symbolic motifs—that encode religious notions (e.g., divine will, moral ethics from Islamic philosophy) and national elements (e.g., Uzbek folklore, nomadic resilience, communal harmony). Through these, Do'st critiques the spiritual stagnation of the Soviet era and advocates for national renewal in the independence period, using language as a cultural conduit to explore existential crises, absurdity, and the synthesis of Eastern traditions with global influences. The research illuminates how these concepts foster a deeper understanding of Central Asian identity, contributing to contemporary discourses on lingvocultural preservation and post-colonial literature.